Construction of Hexagonal Structures Using a 3D Bioprinter Based on Customized G-Code: - Othman, S.A.; Soon, Chin Fhong; Tee, K.S.; Ahmad, M.K.; Nayan, N.; Sultana, N. (International Journal of Integrated Engineering, 2020)
Three-dimensional (3D) bioprinting is adopted from the existing technology of 3D printing that is able to recreate the microenvironment of tissue structures or organs. However, the existing printing mechanism is normally based on slices of a 3D structure in computer-aided slicer software and prints in horizontal and diagonal manners. Such printing mechanism involving soft bioink which does not polymerise in short period of time produces distorted constructs due to the thixotropic properties of the bioink. To circumvent this problem, G-codes for simple 3D bioprinting mechanism were derived. A 3D bioprinter has been developed to implement unidirectional printing for different concentration of bioink. The modified coding was successfully customized for printing single layer to multilayer hexagonal structures. Additionally, the dimension accuracy of the 3D printing in producing similar dimensions of a design in CAD software is highly dependent on the concentration of the bioink applied. The results show that up to 97 % of printing accuracy can be achieved by applying 10: 50 % v/v of alginate/gelatin bioink.